Automated Information Systems as a New Approach to Risk Management of Pharmacotherapy in the Treatment of Epilepsy - V. V. Arkhipov; N. I. Burmistrova (Безопасность и риск фармакотерапии, 2022)
Epilepsy is a fairly common disease which challenges social life, therefore the use of information systems and software to support patients with epilepsy is a promising trend in electronic and mobile medicine. The aim of the study was to analyse data on the existing information systems, devices, and mobile applications used to support patients with epilepsy and control risks associated with pharmacotherapy, and to assess the prospects for the development of information systems to support patients with epilepsy. The results of an advanced search and systematisation of literature and Internet data suggest a high demand for mobile and e-health. Mobile applications for patients with epilepsy have a large share of e-health tools. The applications help to monitor seizures, record the frequency of taking medications, receive advice on emergency treatment of seizures, adjust the dosage regimen, and, in general, help to reduce the risks of anticonvulsant therapy, increase patient compliance and the competence of the participants in the treatment process. The analysis of the convenience and functionality of the foreign-produced mobile applications: Epilepsy Journal, Seizure Tracker, Helpilepsy, Seizure First Aide, did not reveal any significant differences between them. The following shortcomings of the mobile applications were identified: lack of Russian language support (except Epilepsy Journal), lack of advertisement blocking options in free applications, incomplete use of video recording capabilities and location-based systems. Global trends in the development of mobile medicine suggest the need for Russian-produced software that would address the identified shortcomings of the existing foreign applications and help support patients with epilepsy.